YIn0.9Mn0.1O3–ZnO nano-pigment exhibiting intense blue color with impressive solar reflectance. (January 2016) - Jose, Sheethu; Jayaprakash, Anaswara; Laha, Sourav; Natarajan, S.; Nishanth, K.G.; Reddy, M.L.P.
Abstract: The current study reports on the synthesis and characterization of a new inorganic nano-pigment with an intense blue color and high solar radiation reflective properties (70%). The nano-pigment YIn0.9 Mn0.1 O3 –ZnO was synthesized by a sol–gel combustion method and characterized with the aid of X-Ray diffraction, Raman spectroscopy, Magnetic susceptibility, Transmission electron microscopy, UV ndash;vis–NIR diffuse reflectance spectroscopy and CIE-1976 L ∗ a ∗ b ∗ color measurements. The Rietveld refinement of the XRD patterns of the developed nano-pigment disclosed the existence of YIn0.9 Mn0.1 O3 and ZnO in a 1:1 ratio with hexagonal crystal structures. For comparison, YIn0.9 Mn0.1 O3 was also synthesized by the sol–gel combustion route and its optical properties compared with that of YIn0.9 Mn0.1 O3 –ZnO. It is interesting to note that the developed YIn0.9 Mn0.1 O3 –ZnO nano-pigment exhibits superior blue hue ( b ∗ = −40.55) and solar reflectance (R ∗ = 70%) values as compared to the YIn0.9 Mn0.1 O3 nano-pigment ( b ∗ = −22.28, R ∗ = 50%). Most importantly, the potential utility of the nano-pigment as a "Cool Pigment" was demonstrated by coating onto roofing materials like aluminum roofing sheets. Graphical abstract: Highlights: A blue colored nano-pigment was synthesized by a sol–gel combustion method. The nano-pigment exhibits superior blue hue and high solar reflectance. The potential utility of the nano-pigment as a 'Cool Pigment' was demonstrated.